2002
DOI: 10.1200/jco.2002.02.118
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of an Implantable Drug Delivery System Compared With Comprehensive Medical Management for Refractory Cancer Pain: Impact on Pain, Drug-Related Toxicity, and Survival

Abstract: IDDSs improved clinical success in pain control, reduced pain, significantly relieved common drug toxicities, and improved survival in patients with refractory cancer pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
393
0
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 634 publications
(415 citation statements)
references
References 27 publications
11
393
0
11
Order By: Relevance
“…As analgesia after a single IT opioid administration lasts only a few hours, prolonged pain control requires the implantation of a pump and a permanent IT catheter. Although this approach has been shown to provide superior pain control in a randomized controlled clinical trial, 55 the method has not been adopted outside of few specialized medical centers fielding multi-specialty teams consisting of anesthesiologists, neurosurgeons and oncologists, who are able to service the implanted hardware and investigate acute complications, which might be related to the catheter.…”
Section: Pharmacological Rationale For Gene Therapy Targeting the Drgmentioning
confidence: 99%
“…As analgesia after a single IT opioid administration lasts only a few hours, prolonged pain control requires the implantation of a pump and a permanent IT catheter. Although this approach has been shown to provide superior pain control in a randomized controlled clinical trial, 55 the method has not been adopted outside of few specialized medical centers fielding multi-specialty teams consisting of anesthesiologists, neurosurgeons and oncologists, who are able to service the implanted hardware and investigate acute complications, which might be related to the catheter.…”
Section: Pharmacological Rationale For Gene Therapy Targeting the Drgmentioning
confidence: 99%
“…One RCT reported a non-significant trend for shorter survival in patients treated with oral opioids compared with intrathecal opioids for pain control (6 month survival 37% vs. 54%; p=0·06) [66]. Although the intrathecal group had a larger OME dose than the medically managed group, systemically the opioid concentration would be orders of magnitude less.…”
Section: Effect Of Opioids On Survivalmentioning
confidence: 99%
“…There were 3 RCTs, 3 prospective studies and 1 retrospective study (Table 1). These studies tended to be multicentre (Table 1) [18,29,65,66]. The mean sample size was 485 patients.…”
Section: Long Term Studies: Study Characteristicsmentioning
confidence: 99%
“…The authors identified three randomized controlled trials comparing intraspinal with systemic analgesia [2][3][4]. The first study by Vanino et al found no statistically significant difference in pain [2]; the second study by Smith et al revealed a borderline statistical significance of questionable clinical value [3], while the third council study revealed no difference in pain control between epidural and subcutaneous administration of morphine [4]. The methodologic quality of the three included studies needs to be highlighted.…”
mentioning
confidence: 99%
“…Two studies reported no sample size calculations, and both appeared to be under-powered [2,4]. Two were open-label studies [2,3] which could significantly affect how pain and side effects were assessed. Finally, all were supported by pharmaceutical companies.…”
mentioning
confidence: 99%